Research on the Industrial Transfer from the Yangtze River Delta to Linyi City based on the Industrial Gradient Coefficient - TIAN, YANMIN (Pacific International Journal, 2023)
The Yangtze River Delta region, represented by Shanghai, Zhejiang and Jiangsu, has grown as one of the most developed regions in China based on the acceptance of international industrial transfer. However, along with the rising factor costs, increasing environmental pressure and resource constraints, it has become a general trend to upgrade industrial structure, give priority to intensive, high technology and high value-added industries, some labor-intensive and capital-intensive industries is moved to other regions in the country. As the southern gate of Shandong Province, Linyi City is close to the Yangtze River Delta, with a common history, and complementary resources, and is an important hub connecting the north and south economies. It should take full advantage of its location, natural resources and labor resources to actively undertake the industrial transfer of the Yangtze River Delta and participate in the regional economic cooperation and development of the Yangtze River Delta. The difference in the development level between the transferring and taking over places is a prerequisite for industrial transfer, which can be measured by the industrial gradient coefficient, which shows the different levels of industrial gradients to determine the transferring industries in the Yangtze River Delta region; in addition, the relative industrial gradient coefficient is introduced to determine the industries Linyi can take over.